The pursuit of paternal custody - Pieterse, Johanna Tyziena (Rhodes University, Faculty of Humanities, Department of Sociology, 2002)
Issues concerning children may be the most intense and emotive areas of divorce and can lead to spectacular legal battles. Social work practice revealed that it is often the father who leaves the court, stripped of his fatherhood by a court order that only grants him limited access to his own children. Some divorced fathers disengage from their children's lives but there is documented evidence of South African fathers who desire continuity in their relationships with their children after divorce. An interest in these fathers prompted this study. Fathers who challenged maternal custody were selected since it was assumed that their lived experiences would include non-custodial as well as custodial fatherhood. The study was approached from a constructivist position and was further informed by a family systems theory. South African and international literature was perused followed by an exploratory study on the relatively uncharted terrain of paternal custody. A qualitative method was used and one unstructured interview with a schedule was conducted with each of the five respondents who were selected according to non-probability purposive sampling methods. Interviews were recorded and transcribed verbatim. Data was analysed cross-sectionally around certain themes and categories that were extracted from the data. The most significant findings of the study which appear to resemble some earlier national and international findings, are summarised as follows: Some fathers appear to have sound motives for pursuing custody of their children. These fathers, if afforded the opportunity, find fulfilment in parenting their children whom they perceive to be happy and prosperous in their care. There are fathers in whom divorce causes clear and profound signs of distress which appear to be related to the loss of the pre-divorce father I child relationship. The feeling of powerlessness to effect the well-being of their children as they see it was emphasised. Recommendations generated from these findings relate to the elimination of gender bias from custody decisions, including fathers in therapeutic interventions with divorced families and the provision of family courts and mediation services as suggested in the White Paper for Social Welfare. Recommendations for future research are also presented.
Keywords: Custody of children -- South Africa; Paternal custody -- South Africa; Divorced fathers -- South Africa; Father and child -- South Africa